2018
DOI: 10.1186/s12917-018-1560-7
|View full text |Cite
|
Sign up to set email alerts
|

Serum hepatokines in dairy cows: periparturient variation and changes in energy-related metabolic disorders

Abstract: BackgroundDuring peripartum period, dairy cows are highly susceptible to energy metabolism disorders such as fatty liver and ketosis. Angiopoietin-like protein 4 (ANGPTL4) and fibroblast growth factor 21 (FGF21), known as hepatokines, play important roles in lipid metabolism. The purposes of our study were to evaluate variations of serum ANGPTL4 and FGF21 concentrations in periparturient dairy cows and changes in these serum analyte concentrations of energy-related metabolic disorders in early lactation dairy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 54 publications
2
27
0
Order By: Relevance
“…Many studies have found that BHBA is a predominant and stable blood ketone body in ruminant ketosis [4,10], which, therefore, has been widely used for clinically diagnosing and classifying ketosis in dairy cows [11]. Furthermore, a large number of molecular biomarkers have been also identified to be associated with ketosis, such as milk fatty acids [12], serum hepatokines [13], inflammatory biomarkers [14], methylglyoxal [2], metabolites [15], mineral elements [16], protein profiling [17], and amino acids [18] in blood.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have found that BHBA is a predominant and stable blood ketone body in ruminant ketosis [4,10], which, therefore, has been widely used for clinically diagnosing and classifying ketosis in dairy cows [11]. Furthermore, a large number of molecular biomarkers have been also identified to be associated with ketosis, such as milk fatty acids [12], serum hepatokines [13], inflammatory biomarkers [14], methylglyoxal [2], metabolites [15], mineral elements [16], protein profiling [17], and amino acids [18] in blood.…”
Section: Introductionmentioning
confidence: 99%
“…Further elevation in its concentration has been recorded with ketosis and fatty liver disease in cows. 10 Adenoviralmediated overexpression of ANGPTL4 caused severe elevation in the concentration of plasma TG due to decreased VLDL clearance under the fasting conditions in mice. 8 Other supporting evidence demonstrated that the inhibition of ANGPTL4 to LPL in rich-LPL tissues, including adipose tissues, resulted in increasing the plasma TG concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…10 Moreover, the plasma concentration of ANGPTL4 was found to be significantly higher in cows with fatty liver and ketosis than in healthy cows. 10 High concentrations of NEFA, which is an important indicator of NEB, notably stimulates the expression and secretion of ANGPTL4 in bovine hepatocytes in vitro. 11,12 Thus, NEB promotes the expression of ANGPTL4, thereby possibly contributing pathologically to energy metabolism disorders in dairy cows during their peripartum period.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…This disorder causes substantial economic losses due to decreased milk production, longer calving intervals, or removal from the herd (Bobe et al, 2004). The increase in plasma fatty acids due to negative energy balance around parturition is one of the causes of fatty liver, which is often followed by ketosis and insulin resistance (Wang et al, 2018). Recent data from dairy cows with fatty liver also revealed an association between increased plasma fatty acids and hepatic mitochondrial dysfunction (Du et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%